2021
DOI: 10.3390/ijerph18126642
|View full text |Cite
|
Sign up to set email alerts
|

Gaming among Children and Adolescents during the COVID-19 Lockdown: The Role of Parents in Time Spent on Video Games and Gaming Disorder Symptoms

Abstract: It is mainly children and adolescents who are involved in video gaming. The lockdown caused by the COVID-19 pandemic may have further increased their use of video games and, consequently, the risk of gaming disorder (GD) symptoms. However, currently, we do not have exhaustive knowledge of this issue. To fill this gap, the current study aims to analyze video gaming habits in children and adolescents during the lockdown, starting in March 2020 in Italy, the first European country affected by the pandemic. Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 79 publications
(142 reference statements)
3
47
0
1
Order By: Relevance
“…In particular, the current investigation suggests that playing video games in moderation may be a helpful strategy to cope with stress, aversive emotions, and loneliness during a lockdown situation, especially those that encourage physical activity and social interactions [ 20 ]. On the other hand, setting restrictions on the time, place, and content of video games seem to be effective strategies to prevent or reduce symptoms in those children who developed addictive behaviors in this pandemic period [ 45 ]. Parents should also foster alternative avenues for social interaction, meaningful leisure activities, and a wider repertoire of interests among their offspring to maintain the right balance with offline activities in their daily routines [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the current investigation suggests that playing video games in moderation may be a helpful strategy to cope with stress, aversive emotions, and loneliness during a lockdown situation, especially those that encourage physical activity and social interactions [ 20 ]. On the other hand, setting restrictions on the time, place, and content of video games seem to be effective strategies to prevent or reduce symptoms in those children who developed addictive behaviors in this pandemic period [ 45 ]. Parents should also foster alternative avenues for social interaction, meaningful leisure activities, and a wider repertoire of interests among their offspring to maintain the right balance with offline activities in their daily routines [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, setting restrictions on the time, place, and content of video games seem to be effective strategies to prevent or reduce symptoms in those children who developed addictive behaviors in this pandemic period [ 45 ]. Parents should also foster alternative avenues for social interaction, meaningful leisure activities, and a wider repertoire of interests among their offspring to maintain the right balance with offline activities in their daily routines [ 44 , 45 ]. Finally, it is important to ensure that young people have access to mental health resources and provide therapists with training on problematic media use to help them recover from the isolation and stress of the pandemic [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing trend of gameplay time on mobile phones is evident, and the reason for the increased play time may be partly due to the impact of the COVID-19 pandemic. The mobile gaming industry has been growing drastically since its introduction with smartphones and earned a total revenue of $86.3 billion in 2020 [ 63 ]. As the gaming industry continues to prosper during the COVID-19 pandemic, it can be expected that, unlike internet gaming on a PC, the mobile phone gaming industry will continue to grow, attracting more adolescent players.…”
Section: Discussionmentioning
confidence: 99%
“…This was also reported in an Italian study conducted during the lockdown, when gamblers reported not only a decrease in gambling but also the relief they felt because the restrictions meant they could not gamble as before [21]. Auer et al [19] confirmed this situation in a population of Swedish, German, Finnish, and Norwegian citizens, who reported no increase in gambling activity.…”
Section: Introductionmentioning
confidence: 60%